Pencegahan Bullying Melalui Sosialiasasi video Interaktif di SDN 1 Watubelah - Muhammad Nabil Afis; Sahla Nur Aulia Dewi; Shifa Istana Azzahra; Sri Ayu Aljannah; Putri Andini; Khalimatus Sa'diyah; Hema Widiawati (Mathematics Education Study Program, 2025)
Bullying is a serious problem in the school environment that can have a negative impact on students' psychological, social and academic development. SDN 1 Watubelah faces challenges in creating a safe learning environment, so preventive efforts are needed to overcome this problem. This research aims to evaluate the effectiveness of interactive video-based socialization in preventing Bullying, which involves the participation of Muhammadiyah University Cirebon students in community service programs. A qualitative approach using the case study method was used in this research, with data collection techniques through interviews, participant observation and documentation. The research results show that interactive video-based socialization increases students' understanding of the impact of Bullying and builds collective awareness among students, teachers and the community in preventing this behavior. Implementation of this method also increases student participation in discussions and self-reflection, which contributes to positive behavioral changes in the school environment. Thus, the use of interactive videos as an educational medium has proven effective in increasing students' awareness and understanding of Bullying. It is hoped that this program can become a model for other schools in developing more interactive and sustainable Bullying prevention strategies.